CREATIVITY VIS-À-VIS SPEAKING AMONG EXTROVERT AND INTROVERT EFL LEARNERS - Hamid Marashi; Asal Amin Ranjbar (University of Kuningan, 2018)
The study attempts to investigate the relationship between extrovert and introvert EFL learners’ speaking skill and their creativity. For this purpose, 40 male introverts, 40 male extroverts, 40 female introverts, and 40 female extroverts were selected among a total number of 180 through their performance on the Eysenck’s Personality Inventory. Subsequently, the Abedi-Schumaker Creativity Test and a sample PET speaking test were administered to all 160 participants of the study. The Pearson correlation coefficient was subsequently used to check the correlation between speaking and creativity of each group of extrovert and introvert EFL learners. The results indicated that there was a significant correlation between each group’s speaking and creativity. Furthermore, a linear regression was also run to check any predictability pattern. The findings demonstrated that each group’s speaking predicted significantly their creativity. Keywords: creativity, extrovert, introvert, speaking skill